An Epigraphic View on the Dynamics of Amastrian Peripheral Integration in the "Amstriane." - Ching-Yuan Wu (The 154th AIA and SCS Joint Annual Meeting, January 5–8, 2023, 2023)
In literary sources we find Amastris a thriving second-century civitas with a much frequented port and an intellectual community (cf. Plin. Ep. 10.98; Luc. Alex. 26ff; Luc. Tox. 57ff), but what of the land that supported it? The Amastriane, as Strabo calls it (Ἀμαστρίανη", Strab. 12.3.10), had a lot of good boxwood, but beyond this much is unclear. This paper takes an epigraphic perspective to discuss observable dynamics in the Amastriane, in two steps.The first step attempts to visualize Christian Marek's hypothetical Amastrian territorium – an administratively defined Amastriane – with Google Earth Pro, using epigraphic findspot information and geographical features Marek identified for the representation. GPS coordinates of field surveys collated by Peri Johnson are added to identify potential settlement locations active in the first to third centuries CE within Marek's proposed territorium. Through the cross-referencing attempt one can observe a cluster of twelve "Amastrian" inscriptions and two settlement mounds (Ören Höyük & Çengelli) in the Eflani Plateau south of the Küre Mountains. This correlation between two sets of data seems to have gone previously unnoticed in relevant scholarship. This paper assumes that inquiry into this cluster of inscriptions and settlement mounds may lead to further insights on the dynamics of an extensive and rugged territory under the control of a civitas during the Principate.The second step interrogates this group of evidence: what can we learn from the assemblage regarding communal diversity, social relations, institutional participation, and connectivity on the periphery of the Amastriane? Of importance is an inscription that specifically refers to an Amastrian archon who was also a genearch of what appears to be a local clan, found at Meyre (approx. 70 km southeast of Amastris; Marek Kat. Amastris no. 95). Scholars have focused more on the cult that the genearch's family worshipped and naos they built, and less if any on the genos' involvement with Amastrian civic institutions. The second key inscription is for a nomikos Demetrios son of Kyrenios (Marek Kat. Amastris no. 97). He was perhaps related to a Chrestes son of Kyrenios and a self-designated Amastrian of the tribe Halicarnassus, who set up a funerary monument at Deresameail (Marek Kat. Hadrianopolis no. 29; 10 km northeast of Hadrianopolis) for his brother-in-law Sextus Vibius Epaphroditus, perhaps related to the Trajanic primipilarius Sextus Vibius Gallus from Amastrian Kytoros. While Corsten and Ruscu have suggested and commented on these relationships, there remains considerable potential to discuss how such relationships formed despite geography, territorial boundaries, institutional divisions, and other inhibiting factors.This paper wishes to suggest that Marek' expansive Amastrian territorium would have initially been a highly fragmented social and political space, but familial recruitment, manumission, intermarriage, and mobility between significant urban centers gradually created common ground for integration. Also, the clan at Meyre may have benefited from intensifying interaction between Amastris, Hadrianopolis and Pompeiopolis, leading to its increased importance and greater participation in Amastrian institutions and norms.